Improvement of Mechanical Behavior of FSW Dissimilar Aluminum Alloys by Postweld Heat Treatments - S. Prabhu; M. Naga Swapna Sri; P. Anusha; G. Saravanan; K. Kannan; Selvaraj Manickam (Advances in Materials Science and Engineering)
AA6262 and AA5456 alloys are welded through friction stir weld (FSW) with process parameters of tool speed of 1200 rpm, welding speed of 25 mm/min, and tool angle of 3 degree. A cylindrical shape HSS-13 tool is used to perform the welding process To improve mechanical properties of tensile strength (TS), yield strength (YS), elongation%, hardness, and wear behavior, postweld heat treatment was conducted on the FSW sample at different temperatures from 300°C to 500°C. The influence of heat treatment (HT) changes the material characteristics. It is observed that the maximum TS (209 MPa) and YS (178 MPa) are identified when maintaining temperature 350°C on the FSW sample. The reduction in elongation of as-welded joints is entirely improved by HT, and the elongation percentage is almost increased to 5% when increasing temperature on the heat treatment process, and hardness test results exhibited that the increased hardness value (120Hv) is found at HT-300°C nugget zone distance of 0 to 5 mm range.